2019
DOI: 10.1163/15707563-00001079
|View full text |Cite
|
Sign up to set email alerts
|

Genetic effects of leptin receptor (LEPR) polymorphism on litter size in a Black Bengal goat population

Abstract: The leptin receptor (LEPR) is involved in central signaling for both energy homeostasis and reproduction. The present study investigates the association of the LEPR gene with the prolificacy of Black Bengal goat. Two single nucleotide polymorphisms (SNPs) in intron 3 and one SNP in exon 4 in the LEPR gene were identified by pooled DNA sequencing. The identified SNPs were genotyped by the direct sequencing method from 84 Black Bengal does. A synonymous mutation (Lysine > Lysine) was found as a polymorphism i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…It is noteworthy that Tibetan goat has other characteristics and traits besides plateau adaptability, such as slow growth, small body size and low fecundity. So, some relative genes were detected, the most special gene was LEPR , which not only related to hypoxic, but was also associated with reproductive and fattiness traits in goats and sheep [ 47 , 48 ]. PROP1 (PROP paired-like homeobox 1) ( di value = 15.53), another strongly selected gene, proved to be associated with growth traits of goat and sheep [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that Tibetan goat has other characteristics and traits besides plateau adaptability, such as slow growth, small body size and low fecundity. So, some relative genes were detected, the most special gene was LEPR , which not only related to hypoxic, but was also associated with reproductive and fattiness traits in goats and sheep [ 47 , 48 ]. PROP1 (PROP paired-like homeobox 1) ( di value = 15.53), another strongly selected gene, proved to be associated with growth traits of goat and sheep [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…This biological pathway is vital in goat breeds in Kenya to maintain adequate energy production and activity in their harsh environment, especially during the lactation period. The LEPR gene is also related to hypoxic in Tibetan goats ( Jin et al, 2020 ) and reproductive and fatness traits in goats and sheep ( Alim et al, 2019 ; Gunawan et al, 2019 ). The parathyroid hormone synthesis, secretion, and action of the KEGG pathway is associated with GNAI2 , PDE4B , and RHOA genes identified in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [ 39 ] reported that, in Porcine, there were strong relationships between intron 2 and exons 2 and 18 polymorphisms and reproductive features. As well as Alim et al [ 40 ] revealed that two SNPs detected within intron 3 and one SNP in exon 4 of LEPR gene and goats with heterozygous genotype AG at the loci g.104911A>G and g.105151A>G showed the highest prolificacy performance when compared with the other, homozygous genotypes. Sun et al [ 41 ] investigated that the majority of studied features in Luchuan and Large White pigs with AA genotype were greater than those with AB and BB genotypes ( P 0.05), according to the association analysis in the analyzed locus of LEPR gene exon 2 and in terms of litter size attributes, the AA genotype outperformed the AB and BB genotypes.…”
Section: Discussionmentioning
confidence: 90%